Improving total saccharification yield of Arabidopsis plants by vessel-specific complementation of caffeoyl shikimate esterase (cse) mutants - Vargas, Lívia (Biotechnol Biofuels, 2016)
BACKGROUND: Caffeoyl shikimate esterase (CSE) was recently characterized as an enzyme central to the lignin biosynthetic pathway in Arabidopsis thaliana. The cse-2 loss-of-function mutant shows a typical phenotype of lignin-deficient mutants, including collapsed vessels, reduced lignin content, and lignin compositional shift, in addition to a fourfold increase in cellulose-to-glucose conversion when compared to the wild type. However, this mutant exhibits a substantial developmental arrest, which might outweigh the gains in fermentable sugar yield. To restore its normal growth and further improve its saccharification yield, we investigated a possible cause for the yield penalty of the cse-2 mutant. Furthermore, we evaluated whether CSE expression is under the same multi-leveled transcriptional regulatory network as other lignin biosynthetic genes and analyzed the transcriptional responses of the phenylpropanoid pathway upon disruption of CSE. RESULTS: Transactivation analysis demonstrated that only second-level MYB master switches (MYB46 and MYB83) and lignin-specific activators (MYB63 and MYB85), but not top-level NAC master switches or other downstream transcription factors, effectively activate the CSE promoter in our protoplast-based system. The cse-2 mutant exhibited transcriptional repression of genes upstream of CSE, while downstream genes were mainly unaffected, indicating transcriptional feedback of CSE loss-of-function on monolignol biosynthetic genes. In addition, we found that the expression of CSE under the control of the vessel-specific VND7 promoter in the cse-2 background restored the vasculature integrity resulting in improved growth parameters, while the overall lignin content remained relatively low. Thus, by restoring the vascular integrity and biomass parameters of cse-2, we further improved glucose release per plant without pretreatment, with an increase of up to 36 % compared to the cse-2 mutant and up to 154 % compared to the wild type. CONCLUSIONS: Our results contribute to a better understanding of how the expression of CSE is regulated by secondary wall-associated transcription factors and how the expression of lignin genes is affected upon CSE loss-of-function in Arabidopsis. Moreover, we found evidence that vasculature collapse is underlying the yield penalty found in the cse-2 mutant. Through a vessel-specific complementation approach, vasculature morphology and final stem weight were restored, leading to an even higher total glucose release per plant. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-016-0551-9) contains supplementary material, which is available to authorized users.